Recent Developments in Natural Product Inspired Synthetic 1,2,4-Trioxolanes (Ozonides): An Unusual Entry into Antimalarial Chemotherapy - Tiwari, Mohit K.; Yadav, Dharmendra K.; Chaudhary, Sandeep (Current Topics in Medicinal Chemistry, 2019)
According to WHO “World health statistics 2018”, malaria alongside acute respiratory infections and diarrhoea, is one of the major infectious disease causing children’s death in between the age of 1-5 years. Similarly, according to another report (2016) malaria accounts for approximately 3.14% of the total disease burden worldwide. Although malaria has been widely eradicated in many parts of the world, the global number of cases continues to rise due to the rapid spread of malaria parasites that are resistant to antimalarial drugs. Artemisinin (8), a major breakthrough in the antimalarial chemotherapy was isolated from the plant Artemisia annua in 1972. Its semi-synthetic derivatives such as artemether (9), arteether (10), and artesunic acid (11) are quite effective against multi-drug resistant malaria strains and are currently the drug of choice for the treatment of malaria. Inspite of exhibiting excellent antimalarial activity by artemisinin (8) and its derivatives, parallel programmes for the discovery of novel natural and synthetic peroxides were also the area of investigation of medicinal chemists all over the world. In these continuous efforts of extensive research, natural ozonide (1,2,4- trioxolane) was isolated from Adiantum monochlamys (Pteridaceae) and Oleandra wallichii (Davalliaceae) in 1976. These naturally occurring stable ozonides inspired chemists to investigate this novel class for antimalarial chemotherapy. The first identification of unusually stable synthetic antimalarial 1,2,4-trioxolanes was reported in 1992. Thus, an unusual entry of ozonides in the field of antimalarial chemotherapy had occurred in the early nineties. This review highlights the recent advancements and historical developments observed during the past 42 years (1976-2018) focusing mainly on important ventures of the antimalarial 1,2,4-trioxolanes (ozonides).
Keywords: 1; 2; 4-Trioxolane